Ultra-high-frequency radio-frequency acoustic molecular imaging with saline nanodroplets in living subjects - Chen, Yun-Sheng; Zhao, Yang; Beinat, Corinne; Zlitni, Aimen; Hsu, En-Chi; Chen, Dong-Hua; Achterberg, Friso; Wang, Hanwei; Stoyanova, Tanya; Dionne, Jennifer; Gambhir, Sanjiv Sam (Nature nanotechnology, 2021)
Molecular imaging is a crucial technique in clinical diagnostics but it relies on radioactive tracers or strong magnetic fields that are unsuitable for many patients, particularly infants and pregnant women. Ultra-high-frequency radio-frequency acoustic (UHF-RF-acoustic) imaging using non-ionizing RF pulses allows deep-tissue imaging with sub-millimetre spatial resolution. However, lack of biocompatible and targetable contrast agents has prevented the successful in vivo application of UHF-RF-acoustic imaging. Here we report our development of targetable nanodroplets for UHF-RF-acoustic molecular imaging of cancers. We synthesize all-liquid nanodroplets containing hypertonic saline that are stable for at least 2 weeks and can produce high-intensity UHF-RF-acoustic signals. Compared with concentration-matched iron oxide nanoparticles, our nanodroplets produce at least 1,600 times higher UHF-RF-acoustic signals at the same imaging depth. We demonstrate in vivo imaging using the targeted nanodroplets in a prostate cancer xenograft mouse model expressing gastrin release protein receptor (GRPR), and show that targeting specificity is increased by more than 2-fold compared with untargeted nanodroplets or prostate cancer cells not expressing this receptor. Ultra-high-frequency radio-frequency acoustic molecular imaging is a safe molecular imaging diagnostic option because it does not require radioactive probes or high magnetic fields, but lack of biocompatible targeted contrast agents has so far limited its in vivo application. In this paper the authors present perfluorocarbon nanodroplets containing hypertonic saline solution for targeted molecular imaging of prostate cancer in animal models.